The role of interleukin-10 in the differential expression of interleukin-12p70 and its beta 2 receptor on patients with active or treated paracoccidioidomycosis and healthy infected subjects - Romano, C. C.; Mendes-Giannini, Maria José Soares [UNESP]; Duarte, A. J. S.; Benard, G. (Elsevier B.V., 2005)
Paracoccidioidomycosis patients present an antigen-specific Th1 immunosuppression. To better understand this phenomenon, we evaluated the interleukin (IL)-12 pathway by measuring IL-12p70 production and CD3(+) T cell expression of the IL-12 receptor (IL-12R)beta1/beta2 chains, induced with the main fungus antigen (gp43) and a control antigen, from Candida albicans (CMA). We showed that gp43-induced IL-12p70 production and IL-12Rbeta2 expression were significantly decreased in acute and chronic patients as compared to healthy subjects cured from PCM or healthy infected subjects from endemic areas. Interestingly, the healthy infected Subjects had higher gp43-induced IL12p70 production and beta2 expression than the cured subjects. The addition of a neutralizing anti-IL-10 antibody to the cultures increased IL12p70 levels and beta2 expression in acute and chronic patients to levels observed in Cured subjects. Conversely, addition of the cytokine IL-10 strongly inhibited both parameters in the latter group. In conclusion, we have shown that paracoccidioidomycosis-related Th1 immunosuppression is associated with down-modulation of the IL-12 pathway, that IL-10 may participate in this process, and that patients cured from paracoccidioidomycosis may not fully recover their immune responsiveness. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: paracoccidioidomycosis; interleukin-12; interleukin-12 receptor; interleukin-10; IL-12R beta 2 chain; immunosuppression